The prognostic value of ultra low-dose thallium myocardial perfusion protocol using CZT SPECT - Bednárová, Veronika; Kincl, Vladimír; Kamínek, Milan; Vašina, Jiří; Panovský, Roman; Máchal, Jan (The international journal of cardiovascular imaging, 2019)
The purpose of this study was to assess the prognostic value of ultra-low dose thallium myocardial perfusion imaging. Three hundred and sixty-six patients (245 men) underwent ultra-low dose stress-redistribution imaging on CZT SPECT camera GE Discovery NM 530c. The stress test was performed by bicycle ergometry or regadenoson injection. The activity of 0.5 MBq (0.014 mCi) Tl-201 chloride per kilogram of body weight was administered. The stress images were acquired immediately and redistribution images were taken after 3 h. Patient follow-up was focused on combined end-point (death, myocardial infarction, unstable angina, revascularization and hospitalization for heart failure). Data analysis was performed from hospital database, with a mean period 23 months. Patients with revascularization within 1 month after SPECT was excluded as revascularization for diagnosis. Ischaemia on SPECT was found in 72 patients, 294 patients were without ischaemia. In patients with ischaemia there were 21 (29.2%) subjects with cardiac events, and 23 (7.9%) in patients without ischaemia (HR 4.15, 95% CI 2.30-7.51, p < 0.0001). Ultra-low dose thallium perfusion imaging using CZT camera provides very good prognostic results in assessment of myocardial ischaemia.
Keywords: Cadmium; Female; Predictive Value of Tests; lidé středního věku; telur; Tellurium; progrese nemoci; dávka záření; Myocardial Perfusion Imaging; radioizotopy thallia; Radiation Dosage; radiofarmaka; kadmium; mužské pohlaví; reprodukovatelnost výsledků; SPECT; Prognostic value; prediktivní hodnota testů; zobrazování myokardiální perfuze; pyrazoly; Gamma Cameras; Humans; časové faktory; jednofotonová emisní výpočetní tomografie; Low-dose; Equipment Design; zátěžový test; Purines; Vasodilator Agents; Prognosis; ischemická choroba srdeční; Pilot Projects; radiační expozice; Pyrazoles; gama kamery; Myocardial perfusion; lidé; zinek; Radiopharmaceuticals; Middle Aged; Thallium; Radiation Exposure; Time Factors; koronární cirkulace; pilotní projekty; senioři; vazodilatancia; Reproducibility of Results; prognóza; Exercise Test; ženské pohlaví; puriny; Disease Progression; Aged; Myocardial Ischemia; design vybavení; Thallium Radioisotopes; Tomography, Emission-Computed, Single-Photon; Zinc; CZT; Male; Coronary Circulation